Collective Innovation Model in the Governance of Increasing Local Own-Source Revenue (PAD) in Makassar City - Firman Pagarra, Muhammad Akmal Ibrahim, Sukri, Hasniati, Didik Iskandar (South Eastern European Journal of Public Health, 2025)
Effective governance of increasing Local Own-Source Revenue will encourage successful development in Makassar City. To realize this, collective innovation is needed so that the target of Local Own-Source Revenue can increase. This study aims to analyze and produce a collective innovation model in the governance of increasing Local Own-Source Revenue (PAD) in Makassar City. This study uses a qualitative research method with an explorative type. Data collection is carried out through observation, in-depth interviews, documentation studies and Focus Group Discussions. Research informants include the Makassar City Regional Revenue Agency, Bank Sulselbar, Taxpayers, PT. Pos Indonesia, Makassar City Bappeda and the Entrepreneurs Association. Data processing includes the stages of data collection, data reduction, data presentation and drawing conclusions. The focus of the research consists of standardization, collaborative engineering, network innovation and openness of innovation. The results of the study indicate that the standardization element in the governance of increasing PAD in Makassar City has various regulations in the form of Laws, Government Regulations, Regional Regulations and Mayoral Regulations as well as SOPs in their implementation. In standardization, these various regulations have sufficiently accommodated the complexity of implementing governance to increase Regional Original Income. The findings of collaborative engineering elements indicate the implementation of collaborative practices by working together with sub-districts and urban villages as well as PT. Pos Indonesia for the collection of Rural and Urban Land and Building Tax (PBB-P2). The network innovation element in the governance of increasing PAD in Makassar City indicates cooperation between the Regional Revenue Agency (Bapenda) and various financial institutions to develop innovative solutions to optimize Regional Original Income. The element of openness to innovation indicates thatThe development of the PAKINTA application is one of the real implementations of the principles of collective innovation. The collective innovation model requires an increase in public engagement not only in the PAKINTA innovation which so far only accommodates tax payments, but public engagement needs to be applied and increased in regional levies to maximize the governance of Makassar City's Original Regional Income.